Il problema delle finalità nel vivente, nella macchina e nella società. Un’analisi epistemologica - Cesaroni, Pierpaolo; Ferrari, Marco (Metapsychologica - rivista di psicanalisi freudiana, 2024)
The Problem of Finalities in the Living, Machine, and Society: An Epistemological Analysis. This contribution will consist of two parts. In the first part, we will explore the field of cybernetics to demonstrate how, in the works of its most prominent representatives, there is an attempt to rehabilitate the concepts of purpose and teleology. This effort coincides with a broader reform of the mechanistic and deterministic views inherited from modern science. We aim to show that the central issue in cybernetics is not merely a critique of modern mechanism and determinism, as much of the existing scientific literature suggests, but rather an expansion and reassessment of these tendencies towards what can be defined as both mechanist/teleological determinism and mechanistic/determinist teleology. In the second part, we will illustrate how the onto-epistemological posture initiated by cybernetics serves as a significant epistemological obstacle to scientific practice across various fields. Drawing primarily from the insights of the French philosopher Georges Canguilhem, as well as recent advances in biology and the research on the epistemology of political concepts conducted by our research group at the University of Padua, we will argue that it is only by critically questioning the broad and abstract theory promoted by cybernetics that we can engage in meaningful scientific reflections on the question of finalities. This approach allows us to preserve the complex potential embedded in this question when it is appropriately examined within the unique contexts of different epistemic domains, such as biology and the social and political sciences.